Validity and reliability of tests determining performance-related components of wheelchair basketball - de Groot, S.; Balvers, I. J. M.; Kouwenhoven, S. M.; Janssen, T. W. J. (Journal of Sports Sciences, 2012)
The purpose of this study was to investigate the reliability and validity of wheelchair basketball field tests. Nineteen wheelchair basketball players performed 10 test items twice to determine the reliability. The validity of the tests was assessed by relating the scores to the players' classification and competition standard, and rating of coach and player. Six field tests' test-retest showed good reliability (Intraclass correlation coefficient (ICC) = 0.80-0.97), while the pass-for-accuracy, free throws, lay-up and spot shot showed weak to moderate reliability (ICC = 0.26-0.67). Most tests showed moderate to good validity (r > 0.60). The results suggest that wheelchair basketball field tests are reliable and valid with the exception of the shooting and passing items, which should be interpreted carefully.